IMPLEMENTASI AUGMENTED REALITY SEBAGAI ALAT BANTU PADA PENDERITA BUTA WARNA BERBASIS ANDROID - Ganda Yoga Swara (ITP Press, 2019)
Color blindness is a condition where one can not distinguish a certain color that can be distinguished by a person with a normal eye. A person suffering from color blindness may be caused by birth defects or from overuse of drugs. Color blindness has two types: Blind Partial Color that is blind of color of this type can not see two kinds of colors such as red-green, and blue-yellow whereas other types Blind Colors total that people only see black and white (monochromatic) suffered by men, while women are merely as carriers or recessive genes. Regarding Android smartphone camera there are already applications that use Augmented Reality system by using a camera where there will be 2D or 3D objects that will be displayed to real world objects.The AR app will use the Marker based tracking method AR which uses a marker or a two-dimensional object marker that has a pattern to be read through a camera connected to an Android smartphone, usually a black and white square illustration with a thick black border and a white background.